1999
DOI: 10.1095/biolreprod60.4.783
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody against Chorion Proteins of the Sea Bass Dicentrarchus labrax (Linnaeus, 1758): Studies of Chorion Precursors and Applicability in Immunoassays

Abstract: The monoclonal antibody DLE7 was obtained against 44- to 50-kDa polypeptides solubilized from the vitelline envelope of the Mediterranean sea bass Dicentrarchus labrax. In Western blot analysis of chorion lysates it recognized cross-reactive bands at 44 kDa, 48 kDa, and 110 kDa. Previous affinity blotting with concanavalin-A showed that most of solubilized bands were glycosylated. Enzymatic deglycosylation of chorion proteins followed by Western blot analysis with DLE7 showed that the 48-kDa and 110-kDa antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Occasionally this occurs after formation of covalently linked heterodimers (VE␣-VE␥ and VE␤-VE␥) but before incorporation of VE proteins into the VE. This would be consistent with the suggestion that soluble VE precursor proteins are converted into insoluble VE proteins at the site of envelope assembly in the ovary, not in the liver or bloodstream (8,17,21,(23)(24)(25)(26)(27). Furthermore, the evidence is consistent with a recently proposed mechanism for ZP assembly in mammals that involves short hydrophobic patches near the C terminus (external hydrophobic patch (EHP)) and within the ZP domain (internal hydrophobic patch (IHP)) of ZP precursor proteins (28).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Occasionally this occurs after formation of covalently linked heterodimers (VE␣-VE␥ and VE␤-VE␥) but before incorporation of VE proteins into the VE. This would be consistent with the suggestion that soluble VE precursor proteins are converted into insoluble VE proteins at the site of envelope assembly in the ovary, not in the liver or bloodstream (8,17,21,(23)(24)(25)(26)(27). Furthermore, the evidence is consistent with a recently proposed mechanism for ZP assembly in mammals that involves short hydrophobic patches near the C terminus (external hydrophobic patch (EHP)) and within the ZP domain (internal hydrophobic patch (IHP)) of ZP precursor proteins (28).…”
supporting
confidence: 88%
“…winter flounder, sea bream, cod, and medaka) (18 -22) are synthesized in the liver under hormonal (estradiol-17␤) control and then transported in the bloodstream as proproteins to the ovary where they form the inner layer of the egg VE. In most instances it would appear that polymerization of fish VE proteins takes place in the ovary (8,17,21,(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…20,21 Using a monoclonal antibody against chorion proteins of the sea bass Dicentrarchus labrax, researchers detected signals in hepatocytes, but the signal did not reveal evident subcellular localization patterns. 22 The present evidence suggested that ZP domain-containing proteins are involved in many important biological processes. ZP2 and ZP3, which are involved in spermadhesion to the zona pellucida, are indispensable in acrosome reaction.…”
Section: Discussionmentioning
confidence: 58%
“…A selection of genes up-regulated by the VHSV infection (comprising probes modulated with the 20 highest FC at least for one developmental stage; "top20" genes) is shown in Table 1. For this selection, two main sets of virus induced genes could be distinguished: (1) "top20" genes induced by the virus, and not among the "top20" genes induced by A. salmonicida at any stage of development (set 1) and (2) genes that are among the "top20" for both pathogens for at least at one stage (set 2) ( Table 1).…”
Section: Responses To Vhsv Infection: Maturation Of the Ifn Response mentioning
confidence: 99%
“…This is in contrast to mammals where the embryo is in an almost sterile environment where pathogen exposure is controlled by the mother. Hence, fish eggs and embryos have to be able to fight efficiently against infections, and must possess active defence mechanisms.In teleost eggs, the first line of defence against invading pathogens is the physical barrier of the chorion and membranes 1,2 . Additionally, the embryonic membranes may express molecules to prevent bacterial and viral invasion, and may lack specific receptors for viral entry.…”
mentioning
confidence: 99%